UNIVERSITY STUDENTS’ PERCEPTIONS AND USE OF CAMPUS GREEN SPACES AT GOMBE STATE UNIVERSITY, GOMBE STATE, NIGERIA - Wunubo, Bala; Adamu, Jafun; Audu, Mohammed Usman; Idah, Yina Paul (FUDMA JOURNAL OF SCIENCES, 2022)
Green spaces are essential areas in the university campuses. Attractive green space areas are considered as features which contribute positively not only to the student experience but the image of the university. The study generated data from undergraduate students at Gombe State University, it reveals understandings about students’ perceptions and use of campus green spaces (CGS). The quantitative data collected via the questionnaires were digitalized and analyzed using MS Excel statistic package. Descriptive statistics, including measures of percentage and frequency to analyze the associations between perceptions and use of CGS and students’ well-being on campus. Content analysis was used to analyze qualitative data generated. The study results indicate that majority of respondents (94%) both use and aware of campus green spaces, and CGS are important for the image of the university and also an integral component of the campus environment. The campus aesthetic quality and its design and management style have impact on the perception and use of its green spaces. The students (73%) preferred areas with manicured gardens, seats, and lawns over those areas without these facilities. The study recommends that a university campus needs manifold forms of green spaces to satisfy the needs of increasing number of student users